Diaconal Ministry: History and Theology - Nascimento, Carlos Alexandre do (2021)
Luciano Rocha Pinto is a professor and researcher, with a PhD in History from the Graduate Program in History at the State University of Rio de Janeiro (PPGH-UERJ), with a Post-Doctorate in History from the Fluminense Federal University (PPGH-UFF) and post-doctorate in Theology at the Pontifical Catholic University of Rio de Janeiro (PUC-Rio). He works in the area of ​​political history, pastoral power in the west, and sacred space perspectives. In addition to exercising the diaconal ministry in the Archdiocese of São Sebastião in Rio de Janeiro, he also carried out research on the Permanent Diaconate. With the book, the author presents the Diaconal Ministry in the historical and theological perspective. For about a thousand years the diaconate was lived, in the West, only as a stage for those who were preparing for the presbyterate. With the advent of the Second Vatican Council, the ministry was restored, being replaced as an integral part of the clerical body of the Latin Church. The permanent deacon is the servant of charity, liturgy and the word. In Brazil the number of candidates and ordained is growing, today the national reality has almost 4,000 deacons, according to the National Commission of Deacons of Brazil (CND). Thus, this work aims to signal the paths and present some reflections on the diaconate in its historical formation and theological identity. For the author, the deacon emerges as a bridge and mediation of hope for those who agonize in individualism and materialism. And to understand and live this ministry well, to embrace its theology, mystagogy, it is fundamental and equally important to know the past, in order to live the present well.